Helicobacter Pylori and Gastroduodenal Lesions in Chronic Kidney Disease: Clinical Insights and Therapeutic Approaches - o’g’li, Raupov Abdurahmon Ortiq (American Journal of Bioscience and Clinical Integrity, 2025)
Recent decades have witnessed a growing interest in studying gastroduodenal pathology in patients with chronic kidney disease (CKD). The present paper summarizes the clinical, endoscopic, and morphological features, as well as diagnostic and therapeutic strategies for lesions of the esophagogastroduodenal zone in CKD. Chronic gastritis, erosive gastroduodenitis, and ulcerative lesions are commonly observed, especially in advanced CKD stages, often with mild or latent clinical manifestations. Endoscopic findings frequently include lymphocytic gastritis, antral mucosal erosions, and hemorrhagic changes. The prevalence and pathogenic role of Helicobacter pylori infection remain controversial among CKD patients, including those on hemodialysis. Despite variable eradication success rates, the Maastricht triple therapy regimen—clarithromycin, amoxicillin, and a proton pump inhibitor—remains the standard of care, with dosage adjustments required for renal dysfunction. Early eradication of H. pylori before initiating hemodialysis or kidney transplantation is essential to prevent gastrointestinal bleeding and perforation. The absence of CKD-specific treatment guidelines underscores the need for individualized therapeutic and preventive strategies. Further research is necessary to clarify etiopathogenic mechanisms and optimize diagnostic and treatment algorithms in this high-risk patient population.